10.FREQUENCY OF TYPE 2 DIABETES IN YOUNG AGE GROUPS IN NORTHERN IRAQ (Iraqi Journal of Medical Sciences, 2018)
Background: Type 2 diabetes (T2D) is frequently encountered among younger ages during last decades in both developed and developing countries largely contributed to the increasing degree and prevalence of obesity in such ages.Objective: To determine the frequency of T2D in patients younger than 40 years at Northern Iraq.Methods: Retrospectively a total of 9331 patients were studied consisted of 3471 males and 5860 females with diabetes mellitus (DM) at two settings in Northern Iraq in a period from January 2009 – January 2015. Demographic measurements and clinical evaluation were performed for all patients. The diagnosis of DM and its types was depended on the clinical background and confirmed by plasma glucose level measurement. The data from all patients were assessed and statistically analyzed. Results: T2D contributed by 8704 (93.3%) of total number of study sample. The mean values for body weight and body mass index for T2D were higher than those of T1D patients (78.0±14.2, and 30.93±5.42 vs. 56.1±22.6 and 23.72±6.89) respectively. The female to male ratio in T2D was approximately 1.73:1.00. Out of 8704 patients with T2D, almost 2134 (24.52%) patients were ? 39 years of age. Conclusion: Type 2 diabetes appears to be seen more frequently in younger age groups in Northern Iraqi society in parallel to increased rate of obesity particularly in adolescent and children.Keywords: Diabetes in young, obesity and diabetes, type 2 diabetes.Citation: Alhabbo DJ, Saeed ID, Khalaf YA. Frequency of type 2 diabetes in young age groups in Northern Iraq. Iraqi JMS. 2018; Vol. 16(1): 66-73. doi: 10.22578/IJMS.16.1.10
Keywords: Diabetes in young; obesity and diabetes; type 2 diabetes